2000
DOI: 10.3354/meps193271
|View full text |Cite
|
Sign up to set email alerts
|

Above- and below-ground production, biomass and reproductive ecology of Thalassia testudinum (turtle grass) in a subtropical coastal lagoon

Abstract: Above-and below-ground growth, biomass, phenology and reproductive effort in the seagrass Thalassia testudinum were monitored monthly for 2 yr in the Lower Laguna Madre, Texas. Annual whole plant production (953 i 136 g DW (dry weight) m-2 yr-l) was calculated from monthly measurements of leaf and rhizome production made using marking techniques. Leaf growth exhblted a seasonal pattern; monthly production ranged from 8 to 95 g DW m-' mo-', equivalent to 614 * 71 g DW m-' yr-l.Rhlzome growth was seasonal, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 7 publications
4
39
0
Order By: Relevance
“…As much as 80 to 90% of the dry weight of T. testudinum is belowground biomass (Van Tussenbroek 1998, Kaldy & Dunton 2000, and the belowground fraction may extend deeper than 1 m into the sediment (Marba et al 1994). Shallow disturbances (≤10 cm) likely damaged very little of the belowground biomass and rhizome apical or basal shoot meristems and thus the experimental plots recovered quickly due to regrowth of intact short shoots.…”
Section: Discussionmentioning
confidence: 99%
“…As much as 80 to 90% of the dry weight of T. testudinum is belowground biomass (Van Tussenbroek 1998, Kaldy & Dunton 2000, and the belowground fraction may extend deeper than 1 m into the sediment (Marba et al 1994). Shallow disturbances (≤10 cm) likely damaged very little of the belowground biomass and rhizome apical or basal shoot meristems and thus the experimental plots recovered quickly due to regrowth of intact short shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Productivity of seagrass beds in Big Lagoon was also comparable to that of prior studies that took place in Mississippi (Moncreiff et al, 1992), Virginia (Murray and Wetzel, 1987;Hume et al, 2011), south Florida (Nagel, 2007;Yarbro and Carlson, 2008), and Australia (Eyre and Ferguson, 2002;Eyre et al, 2011b), but much higher than rates measured in H. beaudettei patches in the region (Stutes et al, 2007) (Table 2). Since short-term studies can overestimate actual productivity rates, especially if they are performed in very productive times of the year, such as summer, during which seagrass productivity can be as much as 90% higher than in winter (Kaldy and Dunton, 2000), it is necessary to adjust for seasonal changes when estimating annual productivity rates of seagrass communities (Herzka and Dunton, 1997). Our study was conducted between May and Oct. and does not include either the early spring portion of the growing season or winter and fall, when the plants are dormant.…”
Section: -1419mentioning
confidence: 99%
“…Therefore, the relative availability of green and decaying leaves, as well as the herbivore's choice of leaf type, may be important factors determining sea urchin effects within seagrass meadows. This issue has been inadequately investigated, although it can have important consequences for the functioning of ecosystems, depending on the dif ferent interactions between grazers and seasonal changes in the standing plant biomass, production (Duarte 1989, Kaldy & Dunton 2000, and leaf loss dynamics (Francour 1990, Romero et al 1992. Previous studies have suggested that sea urchins preferentially feed on epiphytes (Verlaque & Nédelec 1983, Shepherd 1987, Tomas et al 2005a, Vergés et al 2011, possibly due to their C:N ratios and the absence of refractory plant material.…”
Section: Introductionmentioning
confidence: 99%